2015
DOI: 10.1063/1.4908267
|View full text |Cite
|
Sign up to set email alerts
|

Benzene derivatives adsorbed to the Ag(111) surface: Binding sites and electronic structure

Abstract: Dispersion corrected Density Functional Theory calculations were employed to study the adsorption of benzenes derivatized with functional groups encompassing a large region of the activated/deactivated spectrum to the Ag(111) surface. Benzenes substituted with weak activating or deactivating groups, such as methyl and fluoro, do not have a strong preference for adsorbing to a particular site on the substrate, with the corrugations in the potential energy surface being similar to those of benzene. Strong activa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 78 publications
6
21
0
Order By: Relevance
“…We can observe that an electron charge transfer of 0.17‐0.24e takes place from the NDA molecule to the Ag surface, in agreement with the results for Δ ρ , allowing the formation of some attractive ionic interaction between adsorbate and substrate. A similar observation was reported for the adenine adsorption on Ag(110) and NN ‐dimethylaniline on Ag(111) . In the latter system, the availability of an aromatic ring to give electron charge was related to the fact that the N(CH 3 ) 2 group is a strong activating substituent of benzene.…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…We can observe that an electron charge transfer of 0.17‐0.24e takes place from the NDA molecule to the Ag surface, in agreement with the results for Δ ρ , allowing the formation of some attractive ionic interaction between adsorbate and substrate. A similar observation was reported for the adenine adsorption on Ag(110) and NN ‐dimethylaniline on Ag(111) . In the latter system, the availability of an aromatic ring to give electron charge was related to the fact that the N(CH 3 ) 2 group is a strong activating substituent of benzene.…”
Section: Resultssupporting
confidence: 74%
“…The h C3 height, which can be taken as a measure of the distance between the NDA aromatic ring and the Ag surface, is in the 2.5‐2.9 Å range and follows the S‐111 > S‐110‐a > S‐110‐b height order. These values can be compared to those corresponding to the adsorption of a molecule with aromatic structure and an amino‐like substituent such as NN ‐dimethylaniline adsorbed on Ag(111) where an E ads value of −1.15 eV and a molecule‐surface distance of 2.87 Å were obtained for a stacking configuration. In another comparison, the aromatic nucleobase adenine adsorbed on Ag(110) exhibits an E ads value of −0.32 eV and a molecule‐surface distance of 2.57‐2.63 Å also for a stacking configuration …”
Section: Resultsmentioning
confidence: 99%
“…The planarity mimicked the adsorption to the gold surfaces and the structure in the crystal. It was shown previously that gold surfaces had little interactions with the adsorbates, which justified our computational approach . Furthermore, the planar symmetry provided a clear σ–π separation, which was useful in our analysis.…”
Section: Computational Detailssupporting
confidence: 62%
“…19 In fact, studies of benzene on various metal surfaces have also shown that the variations in the PES with the different adsorption sites, top (T), bridge (B), and hollow (H), is fairly small, on the order of a few tens of meV. 19,[29][30][31][32][33] This not only implies that the diffusion barrier is low but it also means that the molecules are not strictly pinned to particular adsorption sites on the surface.…”
Section: A Calculated Structure Models and Epitaxial Considerationsmentioning
confidence: 99%